Perlindungan Hukum Terhadap Penetapan Status Covid-19 Pada Pasien Penyakit Umum Oleh Rumah Sakit Di Kota Medan - Dewi Ervina Suryani (Universitas Islam Sumatera Utara, 2021)
The government poured out the budget of trillions as a form of seriousness in handling the coronavirus outbreak which began to spread in Indonesia in the early of 2020. The amount of subsidized funds for the care of covid-19 patients provided by the government to hospitals is used by rogue hospital personnel to reap huge profits by convicting patients who are suffering from other diseases so that they have the status of covid-19 patients (not covid-19, sentenced to covid-19). This research is a type of normative legal research which is conducted by examining the library materials or secondary data. The secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials used in this study were obtained through books, government publications, internal organizational records, reports, journals, and various sites related to coronavirus. The secondary data obtained are then processed by using library research data collection techniques (library research). The study is then analyzed qualitatively through the descriptive analytical method, so that a general conclusion is obtained about the coronavirus. The results showed that the form of legal protection against the determination of Covid-19 status in patients with general illnesses by hospitals in Medan was in the form of compensation. This refers to the Law Number 8 of 1999 concerning Consumer Protection and Law Number 36 of 2009 concerning Health. Keywords: Legal Protection, Covid-19